The regulation of corticosteroid receptors in response to chronic social defeat. (September 2017) - Zhang, Jia; Fan, Yan; Raza, Muhammad U.; Zhan, Yanqiang; Du, Xiang-Dong; Patel, Paresh D.; Zhu, Meng-Yang
Abstract: Our previous studies demonstrated that chronic social defeat (CSD) up-regulated expression of the serotonin transporter (SERT) and norepinephrine transporter (NET) in the brain, which was mediated by corticosteroid receptors. In the present study we first analyzed the alterations of corticosteroid receptors in different brain regions after the CSD paradigm. The results showed that CSD significantly reduced glucocorticoid receptor (GR) protein levels in the CA1 and dentate gyrus of the hippocampus, as well as in central and basolateral nuclei of the amygdala, which was accompanied by the translocation of GR from cytoplasm to nuclei. CSD also markedly reduced GR mRNA levels and MR immunoreactivity in the CA1, CA3 and dentate gyrus areas of the hippocampus. Conversely, CSD pronouncedly enhanced GR mRNA and protein levels in the dorsal raphe nucleus and locus coeruleus relative to the control. As an extension of our previous studies, in situ hybridization and immunohistochemical staining demonstrated that CSD regimen caused a notable increase of SERT mRNA levels in the dorsal raphe nucleus and increased SERT immunoreactivities in CA1 and CA3 of the hippocampus, as well as those in the basolateral nuclei of the amygdala. Likewise, CSD regimen resulted in an evident enhancement of NET immunoreactivity in the CA1 of the hippocampus and in the basolateral nuclei of the amygdala. Our current findings suggest that GR expressional alterations in response to CSD are complex and brain region-specific, which may correspond to their different functions in these regions. Highlights: CSD significantly reduced GR expression in the hippocampus and amygdala. CSD markedly increased GR expression in the dorsal raphe nuclear and locus coeruleus. CSD notably increased SERT expression in the dorsal raphe nuclear, hippocampus and amygdala. CSD increased NET immunoreactivity in the hippocampus and amygdala. These CSD-induced alterations in GR is brain region-specific and functionally correlated.